Percutaneous Removal of a Cardiac Mass in a Patient with Infective Endocarditis: A Case Report - Koney, Nii; Benmessaoud, Chelsea; Cole, Kalonji Y.; Bulut, Yonca; Yang, Eric H.; Moriarty, John M. (Journal of Pediatric Intensive Care, 2019)
Infective endocarditis (IE) in the pediatric population is uncommon and presents with nonspecific signs. Nonetheless, prompt diagnosis and management are critical given its high mortality rate. We present the case of a 15-year-old boy who initially presented with bilateral multifocal pneumonia and was found to have IE with a right ventricular vegetation. The vegetation was removed percutaneously, obviating a more invasive surgical approach. The patient tolerated the procedure well and rapidly improved following removal of the vegetation. This case report highlights the utility of a novel, minimally invasive approach for the management of cardiac masses.
Keywords: Vegetation; angioVac; infective endocarditis